Association between C reactive protein and obesity: a study in a tertiary care hospital - Mandli, Lavanya (International Journal of Advances in Medicine, 2019)
Background: Obesity and dyslipidemia, especially in children and adolescents coupled with impaired blood glucose metabolism and elevated blood pressure may result in atherosclerosis in the older ages. This study was conducted to assess the association between high levels of CRP with obesity. Methods: Details including height and weight for BMI and serum for C reactive protein estimation was collected for all 134 patients. Results: 60.4% were females and 49.6% were males. Among the obese patients, clinically raised CRP levels was observed in 29.2% and elevated CRP levels in 45.8% levels, while in overweight patients, 21.4% had clinically raised CRP and 46.4% has elevated CRP levels. In normal BMI patients, elevated CRP was seen in 22% and clinically raised in 1.9%. Conclusion: Detection of CRP levels in overweight and obese patients is imperative in the early stages itself to prevent cardiovascular diseases.